Optimalisasi Edukasi Higienitas dan Manajemen Sampah Berbasis Sosialisasi dan Media Visual - Muhammad Zulfakar; Sapar Hidayat. S; Adon Alviandre Sirait; Heri Susanto; Fiqriansyah Raditiya Reinaldy; Argya Midra; Salsabilla Ananda Rindina; Dwi Ismawati; Dea Nathasya Sinulingga; Nayla Septia Navira; Zahra Zahra (Forum Kerjasama Pendidikan Tinggi, 2026)
Environmental and sanitation issues remain critical challenges in rural areas, requiring comprehensive and integrated solutions. This community service program aims to optimize understanding and awareness of Clean and Healthy Living Behavior (PHBS) as well as environmental management from an early age, targeting Early Childhood Education (PAUD) students, 5th and 6th grade elementary school (SD) students, and the general public. The program is implemented using a Participatory Action Research (PAR) approach through three main intervention stages: first, hygiene education for PAUD students through motor skill stimulation such as exercise, direct practice of handwashing with soap (CTPS), and coloring activities; second, integrated socialization at the elementary school level involving simulations of organic and inorganic waste sorting, anti-bullying campaigns, and the importance of general health in schools; and third, the design and installation of visual media in the form of educational signboards displaying the decomposition time of household waste in strategic village locations. The results show a significant impact, with 90% of PAUD students demonstrating improved motor skills and independent sanitation understanding, and more than 85% of elementary students able to accurately practice waste sorting. At the community level, the installation of educational signboards has created a cognitive shock effect, increasing public awareness of the dangers of plastic waste accumulation. In conclusion, the synergy between preventive education in schools and visual campaigns in public spaces is highly effective in promoting sustainable sanitation behavior within the village ecosystem.